Assessment of a new biological complex efficacy on dysseborrhea, inflammation, and Propionibacterium acnes proliferation - Trompezinski S; Weber S; Cadars B; Larue F; Ardiet N; Chavagnac-Bonneville M; Sayag M; Jourdan E (Dove Medical Press, 2016)
Sandra Trompezinski,1 Sophie Weber,1 Benoît Cadars,2 Florence Larue,1 Nathalie Ardiet,1 Marlène Chavagnac-Bonneville,2 Michèle Sayag,2 Eric Jourdan2 1NAOS, Aix-en Provence, 2Direction Scientifique Bioderma (NAOS), Lyon, France Introduction: Acne vulgaris is a common chronic inflammatory disease of the pilosebaceous unit triggered by Propionibacterium acnes. A bakuchiol, Ginkgo biloba extract, and mannitol (BGM) complex has been developed to provide patients with acne with a specific dermocosmetic to be used adjunctively with conventional treatments. Objective: The aim of these studies was to assess the antibacterial, anti-inflammatory, and antioxidative potential of BGM complex and its individual compounds as well as its impact on sebum composition. Methods: The antibacterial, anti-inflammatory, and antioxidative potential of BGM complex and its compounds was assessed through in vitro, ex vivo, and clinical studies. The clinical benefit of BGM complex formulated in a cream was assessed in subjects prone to acne through sebum composition analysis and photometric assessments. Results: Results from the studies showed that the BGM complex has significant antibacterial, anti-inflammatory, and antioxidative properties. At similar concentrations, bakuchiol has up to twice the antioxidative potential than vitamin E. In subjects, BGM complex regulated the sebum composition in acne patients by increasing the level of sapienic and linolenic acid and reducing the level of oleic acid. The reduced number of porphyrins on the skin surface showed that it is also effective against P. acnes. Conclusion: BGM complex provides a complete adjunctive care in patients with acne by targeting etiopathogenic factors of acne: dysseborrhea, inflammation, and P. acnes proliferation. Keywords: acne, antibacterial, anti-inflammatory, antioxidation, cosmetics, sebum